GAVCA Study: Randomized, Multicenter Trial to Evaluate the Quality of Ventricular Catheter Placement with a Mobile Health Assisted Guidance Technique. Issue 2 (4th August 2017) - Thomale, Ulrich-Wilhelm; Schaumann, Andreas; Stockhammer, Florian; Giese, Henrik; Schuster, Dhani; Kästner, Stefanie; Ahmadi, Alexander Sebastian; Polemikos, Manolis; Bock, Hans-Christoph; Gölz, Leonie; Lemcke, Johannes; Hermann, Elvis; et al.
Abstract: BACKGROUND: Freehand ventricular catheter placement may represent limited accuracy for the surgeon's intent to achieve primary optimal catheter position. OBJECTIVE: To investigate the accuracy of a ventricular catheter guide assisted by a simple mobile health application (mhealth app) in a multicenter, randomized, controlled, simple blinded study (GAVCA study). METHODS: In total, 139 eligible patients were enrolled in 9 centers. Catheter placement was evaluated by 3 different components: number of ventricular cannulation attempts, a grading scale, and the anatomical position of the catheter tip. The primary endpoint was the rate of primary cannulation of grade I catheter position in the ipsilateral ventricle. The secondary endpoints were rate of intraventricular position of the catheter's perforations, early ventricular catheter failure, and complications. RESULTS: The primary endpoint was reached in 70% of the guided group vs 56.5% (freehand group; odds ratio 1.79, 95% confidence interval 0.89-3.61). The primary successful puncture rate was 100% vs 91.3% ( P = .012). Catheter perforations were located completely inside the ventricle in 81.4% (guided group) and 65.2% (freehand group; odds ratio 2.34, 95% confidence interval 1.07-5.1). No differences occurred in early ventricular catheter failure, complication rate, duration of surgery, or hospital stay. CONCLUSION: The guided ventricular catheter application proved to be a safe and simple method. The primary endpoint revealed a nonsignificant improvement of optimal catheter placement among the groups. Long-term follow-up is necessary in order to evaluate differences in catheter survival among shunted patients.